Transition Zone Morphology Dynamics of Dissolved Oxygen (DO) in a Salinity‐Impacted Hyporheic Zone - Qihao Jiang; Matthew H. Kaufman; Guangqiu Jin; Hongwu Tang; Junzeng Xu (Geophysical Research Letters)
Abstract Freshwater salinization is a common yet underappreciated environmental problem in rivers, yet how this process impacts the transport of dissolved oxygen (DO) in the hyporheic zone remains unknown. Using flume experiments and numerical simulations, we have demonstrated that the morphological dynamics of the DO transition zone are controlled by the dimensionless number Da·Ra−2, a measure of the rate of aerobic respiration to free convection. At low Da·Ra−2, the oxic front breaks up into fingers which subsequently grow, and leads to accelerating of DO transport and shrinking of the anaerobic zone in the underlying sediment. As Da·Ra−2 increases, the growth rate of the instability decreases, and the DO plume fingers are suppressed and delayed compared with the saltwater‐freshwater interface, the mixing area between saltwater and freshwater. These results indicate that the freshwater salinization syndrome can have significant impacts on the functioning of aquifer ecosystems unless regulated and managed effectively.